Neurologic outcome in patients with cardiac arrest complicating ST elevation myocardial infarction treated by mild therapeutic hypothermia: The experience of a tertiary institution - Aruğaslan, Emre; Karaca, Mehmet; Özcan, Kazım Serhan; Zengin, Ahmet; Tatlısu, Mustafa Adem; Bozbeyoğlu, Emrah; Satılmış, Seçkin; Yıldırımtürk, Özlem; Yekeler, İbrahim; Nurkalem, Zekeriya (Turkish Soc Cardiology, 2016)
Objective: Therapeutic hypothermia improves neurologic prognosis after cardiac arrest. The aim of this study was to report clinical experience with intravascular method of cooling in patients with cardiac arrest resulting from ST-segment elevation myocardial infarction (STEMI). Methods: Thirteen patients (11 male, 2 famele; mean age was 39.6+/-9.4 years) who had undergone mild therapeutic hypothermia (MTH) by intravascular cooling after cardiac arrest due to STEMI were included. Clinical, demographic, and procedural data were analyzed. Neurologic outcome was assessed by Cerebral Performance Category (CPC) score. Results: Anterior STEMI was observed in 9 patients. One patient died of cardiogenic shock complicating STEMI. Mean cardiopulmonary resuscitation (CPR) duration and door-to-invasive cooling were 32.9+/-20.1 and 286.1+/-182.3 minutes, respectively. Precooling Glasgow Coma Scale score was 3 in 9 subjects. Twelve patients were discharged, 11 with CPC scores of 1 at 1-year follow-up. No major complication related to procedure was observed. Conclusion: In comatose survivors of STEMI, therapeutic hypothermia by intravascular method is a feasible and safe treatment modality.

Amaç: Kalp durması sonrası tedavi amaçlı hipotermi uygulamasının nörolojik prognoz üzerine olumlu etkisi gösterilmiştir. Bu yazıda, ST yükselmeli miyokart enfarktüsüne (STYME) bağlı kalp durması geçiren hastalarda damariçi yöntemle yapılan soğutma tedavisine ilişkin çalışmamız sunuldu. Yöntemler: ST yükselmeli miyokart enfarktüsü sonrası kalp durması nedeniyle damariçi yöntemle tedavi amaçlı hipotermi uygulanan 13 hasta (11 erkek, 2 kadın; ortalama yaş 39.6±9.4 yıl) çalışmaya dahil edildi. Klinik, demografik ve soğutma işlemine ait veriler incelendi. Nörolojik takipler Serebral Performans Kategorisi skorlaması kullanılarak yapıldı. Bulgular: Dokuz hastada akut ön duvar miyokart enfarktüsü tespit edildi. Bir hasta kardiyojenik şok nedeniyle kaybedildi. Ortalama kardiyopulmoner canlandırma süresi ve kapı invaziv soğutma süresi sırasıyla 32.9±20.1 ve 286.1±182.3 dakikaydı. Soğutma öncesi dokuz hastada Glaskow Koma Skalası 3 bulundu; 12 hasta taburcu edildi, 11 hastanın bir yıllık takipte Serebral Peformans Kategorisi skoru 1 olarak saptandı. Soğutma işleminden kaynaklanan ciddi komplikasyon gözlenmedi. Sonuç: ST yükselmeli miyokart enfarktüsü sonrası koma halinde bulunan hastalarda damariçi yöntemle yapılan tedavi amaçlı hipotermi faydalı ve güvenli bir tedavi seçeneğidir.
ST yükselmeli miyokart enfarktüsü sonrası gelişen kalp durması nedeniyle tedavi amaçlı hipotermi uygulanan hastalarda nörolojik sonlanım: Üçüncü basamak merkez tecrübesi
WOS: 000375094600003
PubMed ID: 27111307
Keywords: Cardiac Arrest; Therapeutic Hypothermia; Myocardial Infarction; Kalp Durması; Terapötik Hipotermi; Miyokart Enfarktüsü